2021
DOI: 10.36680/j.itcon.2021.020
|View full text |Cite
|
Sign up to set email alerts
|

Towards the implementation of immersive technology in construction – a SWOT Analysis

Abstract: Whilst research of immersive technology has been growing, substantial efforts thus far have been scattered. Conflicting ideas and arguments from scholars provoke uncertainty and questions about the validity of these outputs in fostering more extensive implementation of immersive technology in the construction industry. Consequently, the direction for further developments in research remains unclear. This study aims to identify the status quo of immersive technology adoption in construction. A systematic review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…VR helps bridge the gap between theory and practice by providing immersive environments that simulate real-world construction processes and enhance practical skills. VR environments can present detailed simulations of complex processes [34]. For example, Sepasgozar [23] provided comprehensive details for every construction task, offering twenty-minute modules that demonstrated the complete operation of a piling rig.…”
Section: Bridging the Gap Between Theory And Practicementioning
confidence: 99%
See 1 more Smart Citation
“…VR helps bridge the gap between theory and practice by providing immersive environments that simulate real-world construction processes and enhance practical skills. VR environments can present detailed simulations of complex processes [34]. For example, Sepasgozar [23] provided comprehensive details for every construction task, offering twenty-minute modules that demonstrated the complete operation of a piling rig.…”
Section: Bridging the Gap Between Theory And Practicementioning
confidence: 99%
“…VR can be experienced in several ways, including through headsets and computer screens [34]. Students positively view the implementation of head-mounted devices in the construction curriculum, indicating a favorable perception of its potential bene ts [31].…”
Section: Vr Implementation and Perception In Construction Educationmentioning
confidence: 99%
“…Researchers have carried out SWOT analyses for immersive technologies, identifying these major impacts on stakeholders, design analysis, construction planning, facilities management, and education/training [22]. Strengths such as better perception and productivity are also mentioned, highlighting weaknesses due to hardware limitations and field usability of immersive headsets [112]. However, the authors also alluded to the opportunities that VR and AR are capable of, using them as tools for better communication and integration of activities.…”
Section: The Role Of Immersive Technologiesmentioning
confidence: 99%
“…This resistance is attributed to the slow adoption of new practices by the AEC sector related to experience, age, social influence, and satisfaction affecting the perception of potential users with immersive technologies [14]. Other challenges involve the existing knowledge gap in managing these technologies, companies' low availability of resources, and inconsistent standard practices that hinder their adoption [112]. These barriers for visual technologies must be addressed while developing practical applications relevant to the industry, justifying how they contribute towards the overall project lifecycle rather than only focusing on some areas of a macro process.…”
Section: The Role Of Immersive Technologiesmentioning
confidence: 99%
“…The present study found that government participation in ImTs has been low. Although Moshood et al [96] opined that government rules and regulations could improve the construction industry's performance in terms of innovation implementation, few government-facing studies have been conducted on the implementation of ImTs in the construction industry [79]. Governments can provide funding, tax incentives, mentorship programs, and practical support to foster the growth of ImT ecosystems in the construction industry.…”
Section: Modeling the Path Of Riskmentioning
confidence: 99%